Analisis Rasio Profitabilitas Dan Likuiditas Terhadap Kinerja Keuangan Pada PT Silvia Maindo SPBU 74.90209 Makassar - Virsa Audina Octaviani S (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The type of data used in this research is descriptive quantitative. and the data source of data in this study is primary data, namely data collected and obtained by researchers directly either in the form of reports, documents, and interviews. This study uses financial ratio analysis techniques in the form of profitability ratios and liquidity ratios. The results showed that the financial performance analysis at PT Silvia Maindo SPBU 74.90209 Makassar as measured by the profitability ratio with indicators of GPM, NPM, ROA and ROE has increased every year which shows that the company PT Silvia Maindo SPBU 74.90209 Makassar is able to generate profits for the company. While the financial performance as measured by the liquidity ratio with the Current Ratio, Quick Ratio and Cash Ratio indicators shows that it is quite good even though it has decreased every year, the company PT Sailvia Maindo SPBU 74.90209 Makassar still shows the success of management in covering current debt by using liquid cash.